DENSENVOLVIMENTO INICIAL DE MUDAS DE CAFEEIRO INOCULADAS COM ASPERGILLUS NIGER PARA - ASSUNÇÃO, José Jorge Lopes de; SANT’ANA, Gabriela Rodrigues; BARCELOS, Rian Pereira; GUIMARÃES JÚNNYOR, Wellingthon da Silva; VENDRUSCOLO, Eduardo Pradi (ANAIS DO ENIC, 2024)
-